Risk factors for anastomotic leakage following ileosigmoid or ileorectal anastomosis. (2nd April 2018) - Segelman, J.; Mattsson, I.; Jung, B.; Nilsson, P. J.; Palmer, G.; Buchli, C.
Abstract: Aim: Reconstruction with an ileosigmoidal anastomosis (ISA) or ileorectal anastomosis (IRA) is a surgical option after a subtotal colectomy. Anastomotic leakage (AL) is a problematic complication and high rates have been reported, but there is limited understanding of the risk factors involved. The aim of this study was to assess the established and potential predictors of AL following ISA and IRA. Method: This was a retrospective cohort study including all patients who had undergone ISA or IRA at three Swedish referral centres for colorectal surgery between January 2007 and March 2015. Data regarding clinical characteristics, treatment and outcome were collected from medical records. Univariate and multivariate logistic regression models were used to determine the association between patient and treatment related factors and the cumulative incidence of AL. Results: In total, 227 patients were included. Overall, AL was detected amongst 30 patients (13.2%). Amongst patients undergoing colectomy with synchronous ISA or IRA (one‐stage procedure), AL occurred in 23 out of 120 (19.2%) compared with seven out of 107 (6.5%) after stoma reversal with ISA or IRA (two‐stage procedure) ( P = 0.004). In addition, the multivariate analyses revealed a statistically significantly lower odds ratio for AL following a two‐stage procedure (OR 0.10, 95% CI 0.03–0.41, P = 0.001). Conclusions: This study confirms high rates of AL following ISA and IRA. In particular, a synchronous procedure with colectomy and ISA/IRA carries a high risk of AL.